Pengembangan Media Pembelajaran Berbantuan Movie Maker pada Materi Drama bagi Siswa Kelas XI Sekolah Menengah Kejuruan Madani Marindal I - Suryani, Intan; Ali, Ali; Amaluddin, Amaluddin (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study investigates the development, feasibility, and effectiveness of instructional media utilizing Movie Maker software to support the teaching of drama material for eleventh-grade students at SMK Madani Marindal I. Employing the ADDIE development model—comprising Analysis, Design, Development, Implementation, and Evaluation—the research involved a total population of 46 students, with a purposive sample of 22 participants. The findings indicate that the developed media was deemed suitable for instructional use. Evaluations by media experts revealed a "Very Feasible" score of 89% and a "Feasible" score of 81.3%. Assessments by material experts yielded "Feasible" ratings of 83.3% and 78.6%, respectively. Additionally, feedback from an Indonesian language teacher rated the product as "Very Feasible" with a score of 93.3%. Field trials involving 22 students from the XI TBSM and OTKP classes reported a "Feasible" result with an overall percentage of 77.36%. These results affirm the practicality and relevance of Movie Maker-assisted learning media in enhancing student engagement and comprehension in drama instruction.